Enterprise performance intelligence and decision patterns - Kale, Vivek (New York : CRC Press, 2017)
""Vivek Kale has written a great book on performance management that focuses on decision-making; on continuous, incremental improvement; and on identifying common patterns in becoming a more intelligent organization."--James Taylor, CEO of Decision Management Solutions and author of Real-World Decision Modeling with DMN. Introducing the concepts of decision patterns and performance intelligence, Vivek Kale has written another important book on the issues faced by contemporary organizations.--Gary Cokins, author of Predictive Business Analytics and Performance Management: Integrating Strategy Execution, Methodologies, Risk, and Analytics: Enterprise Performance Intelligence and Decision Patterns unravels the mystery of enterprise performance intelligence (EPI) and explains how it can transform the operating context of business enterprises. It provides a clear understanding of what EPI means, what it can do, and application areas where it is practical to use.The need to be responsive to evolving customer needs and desires creates organizational structures where business intelligence (BI) and decision making is pushed out to operating units that are closest to the scene of the action. Closed-loop decision making resulting from a combination of on-going performance management with on-going BI can lead to an effective responsive enterprise; hence, the need for performance intelligence (PI).This pragmatic book:Introduces the technologies such as data warehousing, data mining, analytics, and business intelligence systems that are a first step toward enabling data-driven enterprises.Details decision patterns and performance decision patterns that pave the road for performance intelligence applications.Introduces the concepts, principles, and technologies related to performance measurement systems.Describes the concepts and principles related to balance scorecard systems (BCS).Introduces aspects of performance intelligence for the real-time enterprises.Enterprise Performance Intelligence and Decision Patterns shows how a company can design and implement instruments ranging from decision patterns to PI systems that can enable continuous correction of business unit behavior so companies can enhance levels of productivity and profitability."--Provided by publisher.
Preface -- Acknowledgements -- Data-driven performance -- Aligning business and IT strategy -- Decision support systems -- Database systems -- Data warehousing systems -- Data mining systems -- Analytics systems -- Business intelligence systems -- Decision patterns -- Performance decision patterns -- Performance intelligence -- Performance management systems -- Balance scorecard -- References -- Index.
Keywords: Performance technology; Decision support systems; Business intelligence